Local and Long-Distance Calling: Conversations between the Gut Microbiota and Intra- and Extra-Gastrointestinal Tract Infections - Denny, Joshua E.; Powell, Whitney L.; Schmidt, Nathan W. (Frontiers in Cellular and Infection Microbiology, 2016)
Preservation of health from infectious diseases depends upon both mucosal and systemic immunity via the collaborative effort of innate and adaptive immune responses. The proficiency of host immunity stems from robust defense mechanisms—physical barriers and specialized immune cells—and a failure of these mechanisms leads to pathology. Intriguingly, immunocompetence to pathogens can be shaped by the gut microbiome as recent publications highlight a dynamic interplay between the gut microbiome and host susceptibility to infection. Modulation of host immunity to enteric pathogens has long been studied where gut bacteria shape multiple facts of both innate and adaptive immunity. Conversely, the impact of gut commensals on host immunity to extra-gastrointestinal (GI) tract infections has only recently been recognized. In this context, the gut microbiome can augment host immunity to extra-GI tract bacterial, viral, and parasitic pathogens. This review explores the research that affords insight into the role of the gut microbiome in various infectious diseases, with a particular emphasis on extra-GI tract infections. A better understanding of the link between the gut microbiome and infectious disease will be critical for improving global health in the years ahead.